Urban Agriculture Education and Youth Civic Engagement in the U.S.: A Scoping Review - Russ, Alex; Gaus, Madeline B. (Frontiers in Sustainable Food Systems, 2021)
Urban agriculture education is increasingly used to foster civic engagement among youth, but little is known about this impact. To start closing this gap, we analyzed peer-reviewed journal articles that focus on civic engagement outcomes among high school-aged students in urban agriculture education in the U.S. Using a rapid scoping review, we identified 10 relevant research articles published between 2004 and 2018. These articles show that urban agriculture education programs engage youth in direct civic actions that benefit communities. For example, young participants of these programs created community gardens and donated food. In addition, these programs can prepare youth for future civic engagement, including by enhancing their understanding of social justice and community assets, and by building their leadership skills. Thus, urban agriculture education programs can be instrumental in fostering current and future youth civic engagement.